Hidden violence against the institutionalized elderly - Garbin, Clea Adas Saliba [UNESP]; Teruel, Gabriela Peres [UNESP]; Saliba, Tânia Adas [UNESP]; Garbin, Artênio José Isper [UNESP] (Centro Universitario Sao Camilo - Sao Paulo, 2018)
The aim of this study was to investigate the occurrence of violent actions performed by caregivers against the institutionalized elderly. This cross-sectional study, deals with an analytical, qualitative, and quantitative research carried out with the caregivers of 38 elderly residents of long-term care facilities in the cities of São Paulo State, Brazil. A questionnaire based on the Caregiver Abuse Screen (CASE) was used. Only one trained researcher performed the study, and all ethical and legal aspects were respected. The quantitative data were analyzed by Epi-Info software, version 3.5.4, and Fisher's tests and ANOVA were applied. The qualitative data were analyzed by content categorization. Among the results, all the CASE's questions showed some affirmative answers, indicating the occurrence of violence, and only 21.1% of caregivers said that they had never committed any violent act. In that sense, the main caregivers actions were “to act in a coarse way” (21%) or “to do nothing that they were able to do for the elderly” (39.5%) to help seniors, aiming to obtain control of situations regarding their aggressiveness and behavior. Additionally, a majority (87%) of the caregivers realized that violence exists in the caregivers physical, psychosocial and negligence domains regarding the institutionalized elderly, mainly in hidden forms.
Viol ncia oculta contra idosos institucionalizados
Keywords: Caregivers; Elderly; Elderly Abuse; Homes for the Elderly; Violence